FTTA System Demo Using Optical Fiber-Coupled Active Antennas - Niels Neumann; Robert Trieb; Stephan Frach; Dirk Plettemeier (Photonics, 2014)
The convergence of optical and wireless systems such as Radio-over-Fiber (RoF) networks is the key to coping with the increasing bandwidth demands due to the increasing popularity of video and other high data rate applications. A high level of integration of optical technologies enables simple base stations with a fiber-to-the-antenna (FTTA) approach. In this paper, we present a complete full-duplex RoF–FTTA system consisting of integrated active fiber-coupled optical receiving and transmitting antennas that are directly connected to a standard single mode fiber optical link. Data rates up to 1 Gbit/s could be shown without advanced modulation formats on a 1.5 GHz carrier frequency. The antennas as well as the whole system are explained and the results of the system experiments are discussed.